Integrable string models and sigma-models of hydrodynamic type in terms of invariant chiral currents - Gershun, V.D. (Вопросы атомной науки и техники, 2007)
We considered two types of string models: on the Riemann space of string coordinates with null torsion and on the Riemann-Cartan space of string coordinates with constant torsion. We used the hydrodynamic approach of Dubrovin, Novikov to integrable systems and the Dubrovin solutions of the WDVV associativity equation to construct new integrable string models of hydrodynamic type on the torsion less Riemann space of chiral currents in the first case. We used the invariant local chiral currents of principal chiral models for SU(n), SO(n), SP(n) groups to construct new integrable string models of hydrodynamic type on the Riemann-Cartan space of invariant chiral currents and on the Casimir operators, considered as the Hamiltonians, in the second case. Розглянуто два типу струнних моделей: на просторі Рімана струнних координат з нульовим скрутом та на просторі Рімана-Картана з постійним скрутом. В першому випадку, ми використали гідродинамічний підхід Дубровіна, Новікова до інтегрованих систем та розв’язок Дубровіна рівняння асоціативності ВДВВ, щоб побудувати нові інтегровані струнні моделі гідродинамічного типу на безскрутному просторі Рімана кіральних токів. У другому випадку використали інваріантні локальні кіральні токи SU(n), SO(n), SP(n)-моделі головного кірального поля, щоб побудувати нові інтегровані струнні моделі гідродинамічного типу на просторі Рімана-Картана інваріантних кіральних токів та на операторах Казіміра, розглянутих як гамільтоніани. Рассмотрены два типа струнных моделей: на пространстве Римана струнных координат с нулевым кручением и на пространстве Римана-Картана с постоянным кручением. В первом случае использовали гидродинамический подход Дубровина, Новикова к интегрированным системам и Дубровина решения ВДВВ уравнения ассоциативности, чтобы построить новые итегрированные струнные модели гидродинамического типа на пространстве Римана киральных токов с нулевым кручением. Во втором случае использовали локальные инвариантные киральные токи в модели главного кирального поля для SU(n), SO(n), SP(n)-групп, чтобы построить новые интегрированные струнные модели гидродинамического типа на Римана-Картана-пространстве инвариантных киральных токов и на операторах Казимира, рассматриваемых как гамильтонианы.